A Statistical analysis on Filmix Corporation - Cancio, Michael; Fuertez, Maria Roneza; Ngo, Gilbert; Roa, Yonnah Marie Caparas (Diliman, Quezon City College of Engineering, 2001)
Ready-mixed concrete, the product of the company, has been revolutionizing the construction industry ever since it was invented. This project will try to find out how to improve the product. Details of the manufacturing process are analyzed on how the concrete is mixed. Quality measures on the process and the materials, such as the testing of the stiffness of the wet concrete and the strength of the hardened product, are also provided in this paper. Identification and verification of the problem analyzed was done through the use of the Streamline Analysis Diagram and Pareto Chart respectively. From these, the result shows that the main problem was the rejection of the samples due to low compressive strength. Three factors, namely, H20 cement ratio, volume of fly ash and the additive used, were tested against two additives : Eucoplast 200VZ and M-400 using the 2 design. Multiple linear regression models, residual and normal probability plots were used to obtain the optimum design mix with the least variability. It is recommended that the company tests the other additives and insignificant factors to find out what can give them the optimal design mix.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering
Keywords: Statistics